Food price volatility in Africa: Has it really increased? - Minot, Nicholas (International Food Policy Research Institute, 2012)
The food price crisis of 2007–2008 and recent resurgence of food prices have focused increasing attention on the causes and consequences of food price volatility in international food markets and the developing world, particularly in Africa south of the Sahara. In this paper, we examine the patterns and trends in food price volatility using an unusually rich database of African staple food prices. We find that international grain prices have become more volatile in recent years (2007–2010) but no evidence that food price volatility has increased in the region. This contrasts with the widespread view that food prices have become more volatile in the region since the global food crisis of 2007–2008. In addition, the results suggest that price volatility is lower for processed and tradable foods than for nontradable foods, that volatility is lower in the largest (usually the capital) cities than in secondary cities, and that maize price volatility is actually higher in countries with the most active intervention to stabilize maize prices. These findings suggest that greater attention should be given to the (high) level of food prices in the region rather than volatility per se, that regional and international trade can play a useful role in reducing food price volatility, and that traditional food price stabilization efforts may be counterproductive.